Sistem Pakar Diagnosis Hama dan Penyakit pada Tanaman Padi menggunakan Metode Certainty Factor - Hutabarat, Fatur Padilla; Nasution, Yusuf Ramadhan (MEANS (Media Informasi Analisa dan Sistem), 2024)
This study aims to develop a web-based expert system application using the Certainty Factor method to diagnose pests and diseases in rice plants. The system is designed to assist farmers, particularly in the Barus Subdistrict, Central Tapanuli Regency, in identifying and addressing pest and disease issues that frequently affect rice crops. The development process includes analysis, design, implementation, and testing of the application. Testing results indicate that the application successfully identifies pests and diseases with an accuracy rate of 95%, based on comparisons with manual diagnoses provided by experts. Additionally, the application is user-friendly, allowing farmers to easily select symptoms present in their rice plants and receive accurate diagnoses and appropriate solutions. The user-friendly interface further enhances the ease of use. This study differs from previous research in terms of the types of pests, symptoms, solutions, and the research location.